Magnesium-Mediated Regioselective Additions of Bromoform to Quinone Methides and Aurone-Derived Azadienes - Kumar, Deepak; Satam, Nishikant; Namboothiri, Irishi N. N. (Synthesis, 2024)
The magnesium-mediated addition of bromoform to conjugated electron-deficient alkenes and imines, such as para-quinone methides (p-QMs) and aurone-derived azadienes, respectively, is reported here for the first time. While p-QMs undergo exclusive and hitherto unreported 1,6-addition of bromoform to afford benzylic tribromomethylated diarylmethanes, aurone-derived azadienes undergo both 1,2- and 1,4-additions to furnish α- and γ-tribromomethylamines. A mechanism involving the intermediacy of the tribromomethyl radical has been proposed based on control experiments and EPR studies. Representative synthetic transformations have also been carried out.
Keywords: magnesium-mediated addition; bromoform; conjugate addition; p-quinone methides; azadienes; diarylmethanes